THE IMPLICATIONS OF ASEAN ECONOMIC COMMUNITY (AEC) TO THE REGULATION OF COOPERATIVE SUPERVISION BY THE GOVERNMENT UNDER LAW NUMBER 25/1992 ON COOPERATIVE - Suryokumoro, Herman (Brawijaya Law Journal, 2017)
The applicability of AEC has a profound impact on the development of economic policy in ASEAN countries, including in cooperatives. This paper examines important aspects related to the effect of MEA on cooperative policy in particular on cooperative oversight/supervision by the government. The supervision of cooperatives in Indonesia experienced a shift from de-officialisasi towards autonomy or independence of cooperatives. It is argued that Law No 25 Year 1992 on Cooperative is silent on the government oversight regulation for cooperative. With the AEC government oversight should not be eliminated completely because supervision aims at ensuring the quality and the cooperative to compete in the free market of AEC. Thus, the Law No. 25 Year 1992 could no longer be used as a basis of reference to deal with AEC. This paper proposes that Indonesian Cooperative Board (Dekopin) should have jurisdiction in supervising cooperative. Such supervision is done by promoting the strengthening of the cooperative that maintains the identity of cooperatives.